Analysing the pragmatic content in the conversation sections in Indonesian ELT textbooks / Eka Siswantara and Kamisah Ariffin - Siswantara, Eka; Ariffin, Kamisah (Universiti Teknologi MARA, 2021)
Pragmatic competence is a core part of communicative competence and has become the main focus of teaching and learning process in today’s English language teaching. Thus, it is pivotal to have more of pragmatic materials in English textbooks since they are the major references used in the classroom. This study examined the conversation section in the series of Indonesian ELT textbooks to see whether the pragmatic content as required in the curriculum is fulfilled. Using Searle’s speech acts model as the framework, content analysis method was applied by using descriptive approach in analyzing the elocutionary acts and forces pro-vided in the textbooks. The findings indicate that despite their occurrences on the textbooks, some of the speech acts provided were low in frequency and lacked variety to develop better pragmatic competence for the students. This has significant implications on the textbook writers in developing content materials for the pragmatic competence.